Information as a consumer protection instrument on the consumer credit market - Czechowska, Iwona Dorota; Paduszyńska, Marta; Jędrzejczak, Ryszard; Sadowski, Adam (Technological and Economic Development of Economy, 2024)
The aim of the article was to assess the opinions of consumer credit borrowers on the information message provided to them by lenders at the pre-contractual stage. The opinions were presented in the context of the demographic characteristics of the respondents. The research question posed was whether, taking into account demographic characteristics, the assessment of consumer credit borrowers regarding the information message obtained at the pre-contractual stage varied. The research methodology included a questionnaire and Computer-Assisted Telephone Interviewing (CATI). For the information analysis, we employed the following non-parametric tests: the chi-square test of independence, the Mann–Whitney U test and the Kruskal–Wallis H test. No significant differences were observed in all the parameters of the assessment of the information message, which means that the answer to the research question was negative. The findings suggest that even though borrowers may positively assess the compliance with the information obligations by lenders, it does not mean that all credit decisions made were rational and appropriate to their financial situation. Our study focused on the consumer protection and employed non-parametric tests to analyze the consumer credit borrowers’ assessment of the information provided to them by lenders. First published online 07 June 2024